Reaktualisasi Ijtihad Sebagai Metode Penetapan Hukum Islam Dalam Menghadapi Transformasi Digital - Raisya Kaila Assyifa Harahap; Anisa Febriani; Siti Azmi Azhar; Rabbany Al Ghifari; Habib Maulana Fansury (Albayan Journal of Islam and Muslim Societies, 2025)
The development of digital technology has brought about fundamental changes in various dimensions of life, including in the realm of Islamic law. Various new phenomena, such as electronic transactions, artificial intelligence, cryptocurrencies, financial technology (fintech), and digital-based religious practices, give rise to legal issues that require more adaptive and contextual normative responses. This study aims to examine the urgency of reactualizing ijtihad as a method for establishing Islamic law in the face of digital transformation, while simultaneously analyzing the relevance of the principles of usul fiqh in addressing various contemporary legal challenges. This study uses a normative legal method with a conceptual approach and library research. Research data were obtained from primary sources in the form of usul fiqh books and Islamic legal literature, and are supported by various scientific journals and relevant previous research results. The research findings indicate that reactualizing ijtihad is a crucial need to maintain the continuity and relevance of Islamic law amidst technological developments, without neglecting the basic values ​​of sharia. In this context, the approaches of maqāṣid al-syarī‘ah, maṣlaḥah mursalah, qiyās, and collective ijtihad play a strategic role as instruments in producing adaptive, moderate, and ummah-oriented Islamic legal provisions in the digital era. This finding aligns with various contemporary studies that emphasize the importance of integrating usul fiqh and maqāṣid al-syarī‘ah in responding to technological developments and various new legal issues in the digital era.